Ultrastructural assessment of the CA1 hippocampal neuronal changes in curry leaves extract treated rats subjected to chronic cerebral hypoperfusion - Azzubaidi, Marwan Saad; Mohd Noor, Noriah; A.Talib, Norlelawati; Saxena, Anil Kumar; Al-Ani, Imad Matloub Dally; Maideen, Mohd Maizam (2012)
Curry leaves VIZ. Murraya koenigii leaves (MKL) extract was found to possess robust antioxidant and anticholinesterase activities. Its memory enhancing effect in preclinical studies has also been reported. The current study was designed to evaluate the ultrastructural neurodegenerative changes within CA1 subfield of the hippocampus that result from chronic cerebral hypoperfusion (CCH) in rats, and to assess the possible preventive potential of MKL treatment to these changes. Rats were divided into sham-control, CCH and CCH+MKL treated groups. Ten weeks after surgical induction of CCH rats’ hippocampal sections were processed for transmission electron microscopical examination of CA1 subfield. Sham-control group exhibited normal pyramidal neurons with intact nuclei and abundant cytoplasmic organelles. CCH group hippocampi showed a mixture of necrotic and apoptotic neurodegeneration of pyramidal neurons with extensive loss of cytoplasmic organelles. Thickening of the endothelial basement membrane was observed with evident hypertrophy of astrocytic processes which constitute the vascular end-feet. CCH+MKL treated group demonstrated predominant apoptotic neurodegeneration. The pyramidal cells’ nuclei were shrunken with occasional formation of apoptotic bodies. Distorted intracellular organelles and abnormally thickened capillary endothelial basement membrane was noticed too. In conclusion, MKL treatment could not protect the CA1 hippocampal subfield from the CCH induced ultrastructural neurodegenerative changes.